2015
DOI: 10.1002/art.38945
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Excitatory and Inhibitory Brain Metabolites as Targets of Motor Cortex Transcranial Direct Current Stimulation Therapy and Predictors of Its Efficacy in Fibromyalgia

Abstract: Objective Transcranial direct current stimulation (tDCS) has been shown to improve pain symptoms in fibromyalgia (FM), a central pain syndrome; the underlying mechanisms are not well understood. Our objective was to explore the neurochemical action of tDCS in the FM brain using proton magnetic resonance spectroscopy (1H-MRS). Methods Twelve patients with FM underwent sham tDCS over the left motor (anode) and contralateral supraorbital cortices (cathode) (M1-SO) for 5 consecutive days, a 7 day washout period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 25 publications
6
57
0
1
Order By: Relevance
“…Specifically, the ACC has been reported to be a pain‐intensity encoding region in both healthy volunteers and in animal models (Apkarian, Baliki, & Geha, ; Duerden & Albanese, ; Farrell, Laird, & Egan, ; Senapati et al, ). In addition, recent metabolic studies indicated that chronic knee osteoarthritis pain and fibromyalgia were associated with reduced levels of the inhibitory neurotransmitter GABA in the ACC, which was thought to reflect a disinhibition mechanism of this region in pain perception (Foerster et al, ; Reckziegel, Raschke, Cottam, & Auer, ). Further, the PFC has been shown to exert inhibitory control on the medial thalamus‐ACC loop (Cauda et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the ACC has been reported to be a pain‐intensity encoding region in both healthy volunteers and in animal models (Apkarian, Baliki, & Geha, ; Duerden & Albanese, ; Farrell, Laird, & Egan, ; Senapati et al, ). In addition, recent metabolic studies indicated that chronic knee osteoarthritis pain and fibromyalgia were associated with reduced levels of the inhibitory neurotransmitter GABA in the ACC, which was thought to reflect a disinhibition mechanism of this region in pain perception (Foerster et al, ; Reckziegel, Raschke, Cottam, & Auer, ). Further, the PFC has been shown to exert inhibitory control on the medial thalamus‐ACC loop (Cauda et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to substance P, elevations in CNS glutamate levels in fibromyalgia, measured both in the CSF (Sarchielli et al, 2007) and directly in the brain using proton spectroscopy (H-MRS) are also found in individuals with fibromyalgia (Harris et al, 2009, Fayed et al, 2010, Harris, 2010). In fact, using proton magnetic resonance spectroscopy, glutamate levels in fibromyalgia patients are also elevated in key pain-processing areas of the brain such as the insula and change in response to changes in both clinical and experimental pain when patients are successfully treated (Harris et al, 2008, Harte et al, 2013, Foerster et al, 2015). For example, pregabalin decreases glutamatergic activity in the insula and decreases functional connectivity between the default mode network and insula in individuals with fibromyalgia (Harris et al, 2013).…”
Section: Evidence For Enhanced Excitation In the Central Nervous Systemmentioning
confidence: 99%
“…In a typical study, Foerster and colleagues administered tDCS to 12 patients with fibromylagia. 22 The dosage consisted of 2.0 mA with the anodal electrode placed over the left motor cortex (M1) and the cathodal electrode placed over the contralateral right supraorbital cortex (~Fp2) (Figure 2). Compared to the sham condition, when patients received the active tDCS treatment, a significant decrease was observed in clinical pain scores.…”
Section: Therapeutic Usesmentioning
confidence: 99%